PENGEMBANGAN MEDIA PEMBELAJARAN MATERI SISTEM KOORDINAT BERBASIS GEOGEBRA DI SEKOLAH DASAR - Ulfiyani Ulfiyani; Zetra Hainul Putra; Eddy Noviana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims to develop coordinate system learning media in the form of GeoGebra Applets for fifth grade elementary school students. Learning media was developed using the Research and Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). From the results of validation tests carried out by 3 experts, the results of the first validation obtained a percentage of 77.75% (valid). After revisions/improvements were carried out, the results of the second validation obtained a percentage of 93.65% (very valid). From the results of the one-by-one trial, students gave positive responses when learning the coordinate system using the GeoGebra Applet that had been developed. The results of the practicality test carried out with 3 teachers and 10 students obtained a percentage of 83.42% (very practical). Based on the results of validation tests, one-by-one trials, and practicality tests, the GeoGebra-based coordinate system material learning media for 5th grade elementary school students is suitable for use in the learning process.